Perlindungan Pekerja Migran di Sektor Domestik dalam Situasi Pandemik Covid-19 Bagaimana Asean Mengatasinya? - Arini Azka Muthia Muthia (UNIB Press, 2022)
ASEAN countries are sending countries and receiving countries for migrant workers in the domestic sector. In a health emergency due to the COVID-19 pandemic, almost everyone faces problems, without prior preparation, must follow and comply the various rules set by the governments of each country in order to save from the threat of Corona Virus Disease 2019 which is very dangerous for health and human life. Likewise, with Migrant domestic worker condition, even though in the Covid-19 pandemic situation, they still have to work. Working as workers in the domestic sector faces unique vulnerabilities during the current health crisis, for example, migrant domestic worker lack of access to health care or social protection measures. This research tries to explore the agreements made by ASEAN countries in protecting migrant workers in the domestic sector during the Covid-19 pandemic. This research applies a juridical-normative approach focusing on the legal materials related to the protection of domestic workers. This research also applies the statute approach. The data were analyzed qualitatively. ASEAN has made the agreements in protecting migrant workers in the domestic sector, and ASEAN member countries must reflect up with the Joint Statement of ASEAN Labor Ministers on Response to the Impact of Coronavirus Dieses 2019 (COVID-19) on Labor and Employment and Asean Consensus on the Protection and Promotion of the Rights of Migrant Workers 2017.